Genuine effects of vote advice applications on party choice: Filtering out factors that affect both the advice obtained and the vote. (May 2019) - Kleinnijenhuis, Jan; van de Pol, Jasper; van Hoof, Anita MJ; Krouwel, André PM
Previous research shows effects of the advice from voting advice applications (VAAs) on party choice. These effects could be spurious because common antecedent factors like prior voting, a voter's prior issue positions and election campaign news may explain both party choice and the opinions someone reports to the VAA, and hence the voting advice obtained from the VAA. Often VAAs will advise users to opt for parties that they were already likely to vote for, based on antecedent factors. Here, three-wave panel surveys and media content data for the Dutch national election campaigns of 2010 and 2012 are employed. In spite of spurious correlations resulting from common antecedent factors, genuine VAA effects show up, especially for doubting voters. Party change based on positive VAA-advice for a party is least likely (a) for voters who already have an abundance of antecedent factors in favour of that party anyway, and (b) for those without a single antecedent factor in favour of that party. Genuine VAA effects imply that VAAs make it less easy for political parties to neglect each other's owned issues, because VAAs weigh issues equally for each party.